2014
DOI: 10.1371/journal.pone.0111882
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among People with Severe Mental Disorders Who Reach Old Age: A Longitudinal Study of a Community-Representative Sample of 37892 Men

Abstract: BackgroundSevere mental illnesses are leading causes of disability worldwide. Their prevalence declines with age, possibly due to premature death. It is unclear, however, if people with severe mental disorders who reach older age still have lower life expectancy compared with their peers and if their causes of death differ.Methods and FindingsCohort study of a community-representative sample of 37892 Australian men aged 65–85 years in 1996–1998. Follow up was censored on the 31st December 2010. Lifetime preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…14 In the sample of Chang and colleagues, 15 year follow-up. 19 The excess mortality in men compared to women in schizophrenia may be related to various factors, such as smoking, 8 substance abuse, 20 and treatment noncompliance, 21 that are all more prevalent in men. A milder disease course in women may be of significance as well, although in later onset cases the reverse may be true.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the sample of Chang and colleagues, 15 year follow-up. 19 The excess mortality in men compared to women in schizophrenia may be related to various factors, such as smoking, 8 substance abuse, 20 and treatment noncompliance, 21 that are all more prevalent in men. A milder disease course in women may be of significance as well, although in later onset cases the reverse may be true.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, a Danish case-register study found that the risk of dementia in bipolar disorder increased with the number of affective episodes (Kessing and Andersen, 2004), and was less marked among patients receiving continuous treatment with lithium (but not with other mood stabilizers) (Kessing et al, 2010). Bipolar disorder has also been associated with increased mortality (Almeida et al, 2014), including death by suicide (Schaffer et al, 2015). A systematic review and meta-analysis of 31 studies that included over 300,000 people with bipolar disorder found that the condition more than doubled the risk of premature death both from natural and non-natural causes (such as suicide or accidents) (Hayes et al, 2015).…”
Section: Cognitive Function In Bipolar Disorder and The Risk Of Demementioning
confidence: 91%
“…However, recent data suggest that the euthymic periods are not entirely free of impairments, and that the long-term outcome of people with bipolar disorder is, in at least some cases, associated with cognitive deficits, poor function, and increased risk of dementia and death (Kessing et al, 1999;Bourne et al, 2013;Almeida et al, 2014;Almeida et al, 2016b).…”
Section: Bipolar Disorder: Preparing For the Futurementioning
confidence: 99%
“…There is burgeoning evidence that individuals with severe psychiatric disabilities experience higher than average rates of chronic and life-threatening diseases, including, among others, diabetes, cardiovascular disease, and pulmonary diseases, all of which lead to premature mortality and elevated rates of morbidity within the United States (Capasso et al 2008;Chacón et al 2011;Chafetz et al 2006;Colton and Manderscheid 2006;Lambert et al 2003;Scott and Happell 2011; Substance Abuse and Mental Health Services Administration 2012; Weber et al 2011) and throughout the world (Harris and Barraclough 1998;Saha et al 2007;Currie et al 2014;Almeida et al 2014). Studies suggests that this excess mortality and morbidity are influenced by problems of healthcare access, socioeconomic, and clinical risk factors (Almeida et al 2014;Druss et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggests that this excess mortality and morbidity are influenced by problems of healthcare access, socioeconomic, and clinical risk factors (Almeida et al 2014;Druss et al 2011). This accumulating evidence has prompted an increased emphasis on improved physical health as an important dimension in promoting recovery (Hutchinson et al 2006; Substance Abuse and Mental Health Services Administration, & Center for Behavioral Health Statistics and Quality 2009; Druss and Mauer 2010), research on new interventions to promote health and wellness (Druss et al 2010a, b), as well as a focus on comprehensive and coordinated treatment (Parks et al 2006;President's New Freedom Commission on Mental Health 2003;Thompson et al 2006).…”
Section: Introductionmentioning
confidence: 99%